A space traveler's guide to the Solar System - Thompson, Mark (Astronomer) (Pegasus Books, 2016)
"Have you ever dreamed of being an astronaut, traveling through the universe on your very own space mission? What would it be like to tour the solar system, visiting the sun and the planets, taking in everything from moons to asteroid belts along the way? What would you see, and how would you feel? What would you eat? How would you navigate and produce fuel? How would you survive? On this epic voyage of discovery, astronomer Mark Thompson takes you on that journey. From how to prepare for take-off and the experience of leaving Earth's atmosphere, to the reality of living in the confines of a spaceship and the strange sensation of weightlessness, this is an adventure like no other. Suit up, strap in, and enjoy the ride!,"--Dust jacket.